2018
DOI: 10.1111/jgs.15633
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Geriatrics Knowledge into a Medical Student Clerkship Using Twitter Poll

Abstract: A controlled, prospective, 2‐year cohort observational study was conducted to test whether weekly geriatric questions delivered through Twitter Poll could improve geriatrics knowledge during an internal medicine clerkship for third‐year medical students. Pre‐ and post‐rotation test results used a modified University of California, Los Angeles geriatric knowledge test that included questions linked to 26 Association of American Medical Colleges geriatric competencies for medical students. Data were analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Types of knowledge and skill development included information acquisition and retention, 32‐44 reflection 45‐47 and professionalism 40,48,49,50,51,52,53,54,55,56,57 . Supporting curricular activities ranged from enhancing student engagement, 58‐68 reducing student anxiety with the taught material 69‐71 to improving communication between faculty and students 69,72,73,74 and between students themselves outside of the classroom 38,69,75,76 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Types of knowledge and skill development included information acquisition and retention, 32‐44 reflection 45‐47 and professionalism 40,48,49,50,51,52,53,54,55,56,57 . Supporting curricular activities ranged from enhancing student engagement, 58‐68 reducing student anxiety with the taught material 69‐71 to improving communication between faculty and students 69,72,73,74 and between students themselves outside of the classroom 38,69,75,76 .…”
Section: Resultsmentioning
confidence: 99%
“…38,69,75,76 Many interventions were evaluated to assess student opinions and attitudes towards inclusion of SoMe within their medical curriculum. 8,14,34,49,70,77,78,79,80,81,82,83,84,85,86,87 Privacy was a focus of 28/58 (48%) SoMe interventions with the use of closed gro ups, 32,45,48,68,70,72,74,75,87,88 private communication platforms such as WhatsApp and WeChat 14,33,34,35,36,37,38,50,51,60,62,66,78,80,81,82,83 and even a bespoke institution-specific SoMe platform. 53 16/58 (28%) studies involved case-based or problem-based learning.…”
Section: Some Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings build on previous work that has demonstrated improvements in knowledge, clinical skills, and empathy among undergraduate and graduate medical trainees. [6][7][8][9][10][11][12][13][14][15] In particular, studies designed to evaluate the perceptions of medical and pharmacy students have demonstrated a positive influence of interprofessional activities with respect to geriatric medicine. Shrader et al 23 described an in-home interview and medication history activity with local volunteers, in which students were assessed on attitudes toward other health professionals before and after the experience, demonstrating gains in the importance in collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Geriatrics Twitter Poll was harnessed for improving Geriatrics knowledge among third year medical students. Students who accessed the Geriatrics Twitter Poll improved their Geriatrics knowledge 2 fold over those who did not use Twitter [6]. Other uses include professional societies that create temporary Twitter accounts to make announcements at their annual scientific meetings while attendees Tweet comments about scientific presentations.…”
Section: Examples Of Twitter For Med/surg Education Include a Radiolomentioning
confidence: 99%